'In the name of humanity': redefining socio-economic assistance in the revolutionary marketplace. (3rd March 2020) - Jarvis, Katie
Abstract: Most studies of socio-economic rights in the French Revolution have focused on how officials and other deliverers of aid struggled to redefine assistance, rather than on how recipients themselves contributed to the idea. In contrast, this article centres on poor Parisian market women called the Dames des Halles to bring to light the voices, discourses, and actions of individuals demanding rights and assistance. The Dames had relied on charity and privilege to conduct their commerce during the Old Regime, but the Revolution upended their advantages. Balancing discourses of humanity and utility, the Dames sought to recalibrate their place in the body politic in order to maintain occupational exemptions, favourable commercial positions, and exceptional access to public space. Their battles reveal how everyday citizens and the National Assembly first struggled to reinterpret socio-economic assistance as corrupt privilege, as the state's civic duty, or as exemptions earned by poor working citizens.